Analysis of Deixis in The Short Story “The Garden of Paradise”: Pragmatics Study - Puspaningrum, Aprilia; Simatupang, Ervina (Universitas Veteran Bangun Nusantara, 2024)
The study aims to investigate the various forms of deixis and their roles within the short story